DAMPAK AKUNTABILITAS, KETERBUKAAN DAN KEIKUTSERTAAN WARGA PADA PENGURUSAN DANA DESA DI NGRANDU, KECAMATAN GEYER, KABUPATEN GROBOGAN - Indah Kusuma Wardani; Yuniatin Trisnawati D.K.W (Program Studi Akuntansi, 2022)
Research was conducted to understand the impact of accountability, openness, and participation of citizens on the management of village funds. The research was conducted in 2019. The number of communities studied as many as 100 residents in Ngrandu Geyer District grobogan regency. How to take samples using the Malhotra formula. Data is collected by means of surveys through deployment using targeted sampling techniques. Multiple linear regression tests are performed to analyze the data. The study found that accountability, openness, and partial participation positively and significantly affected the management of village funds. The R2 Test analysis showed that accountability, openness, and citizen participation affected the management of village funds by 68.5% and the remaining 31.5% was determined by other factors.